Transglutaminase 3 crosslinks the secreted gel-forming mucus component Mucin-2 and stabilizes the colonic mucus layer - Jack D. A. Sharpen; Brendan Dolan; Elisabeth E. L. Nyström; George M. H. Birchenough; Liisa Arike; Beatriz Martinez-Abad; Malin E. V. Johansson; Gunnar C. Hansson; Christian V. Recktenwald (Nature Communications, 2022)
The colonic mucus layer is an organized system providing a physical barrier against pathogens and simultaneously harbouring the commensal flora. Here the authors report that transglutaminase 3 activity contributes to homeostasis of the colonic mucus layer and the lack of this enzymatic activity leads to increased susceptibility against DSS-induced colitis in mice.